Structural Models of the Liquidity Effect - Pagan, A. R.; Robertson, J. C. (The Review of Economics and Statistics, 1998)
In this paper we examine a number of recent studies that claim to have obtained a well-defined liquidity effect using structural VAR models based on broad measures of money. These studies can be distinguished in terms of the identifying restrictions, sample periods, and frequency of data used. We show that estimation of the structural coefficients of all these models can be achieved by instrumental-variable methods, where the instruments are predetermined variables and the estimated structural errors from other equations in the system. Overall, our judgment is that the evidence for a liquidity effect from these studies is much less certain than suggested in the original papers, primarily because of the poor quality of the instruments used in estimation and the sensitivity of the estimates to the sample period used.